Dataset for the study of “Model Lipid Membranes Assembled from Natural Plant Thylakoids into 2D Microarray Patterns as a Platform to Assess the Organization and Photophysics of Light‐Harvesting Proteins” - Meredith, Sophie; Yoneda, Takuro; Hancock, Ashley; Connell, Simon; Evans, Stephen; Morigaki, Kenichi; Adams, Peter (University of Leeds, 2021)
This dataset shows the raw data, analysed data and documentation related to figures and tables from the study "Model Lipid Membranes Assembled from Natural Plant Thylakoids into 2D Microarray Patterns as a Platform to Assess the Organization and Photophysics of Light‐Harvesting Proteins". This includes: absorbance and fluorescence spectra; images from Fluorescence Lifetime Imaging Microscopy (FLIM); images from Atomic Force Microscopy measurements; epifluorescence measurements; analysis of fluorescence data (FLIM); other graphical analyses; tabulated numerical data.
Keywords: FOS: Biological sciences; Botanical chemistry; Biophysics